Sedimentology of Shale Study Guide and Reference Source - Potter, Paul E.; Maynard, J. Barry; Pryor, Wayne A. (Springer New York, 1980)
We wrote Sedimentology of Shale primarily because we lacked a handy, reasonably comprehensive source of information and ideas about shales for students in our sedimentology program. It was also our feeling that the time for shales to receive more study had finally arrived. Sedimentology of Shale also seems very timely because today more sedimentologists are interested in shales. Certainly in the last five years the pace of shale research has no ticeably quickened because the role of shales as important sources of oil, gas, heavy metals and as a long understudied part of the earth's geologic his tory has been recognized. Noteworthy developments include the elucida tion of the importance of trace fossils in shales, the discovery of thick sequences of overpressured shales in regions such as the Gulf Coast (which have important implications for hydrocarbon migration and faulting), the ex tension of the principles of metamorphic facies to the realm of low tempera ture diagenesis by study of the organic matter in shales, and shales as ul timate sources for mineral deposits. Accordingly, we decided it was timely to write a book on shales. In one respect, however, ours is an unusual book. Most books in geology are produced after one or two decades of progress have been made in a field and attempt to summarize and evaluate that progress
Keywords: Earth Sciences; Sedimentology; Geology; Mineralogy; Earth sciences; Sedimentologie; Schiefer